2014
DOI: 10.1051/0004-6361/201424284
|View full text |Cite
|
Sign up to set email alerts
|

Early evolution of the extraordinary Nova Delphini 2013 (V339 Del)

Abstract: Aims. We determine the temporal evolution of the luminosity (L WD ), radius (R WD ) and effective temperature (T eff ) of the white dwarf (WD) pseudophotosphere of V339 Del from its discovery to around day 40. Another main objective was studying the ionization structure of the ejecta. Methods. These aims were achieved by modelling the optical/near-IR spectral energy distribution (SED) using low-resolution spectroscopy (3500-9200 Å), UBVR C I C and JHKLM photometry. Important insights in the physical conditions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 26 publications
(34 reference statements)
6
69
0
Order By: Relevance
“…These were no longer present by day 14.76. In the optical, Skopal et al (2014) found that the Hα line displayed a P Cygni profile, with terminal velocity −1600 km s −1 at t 0.95 d, decreasing to −730 km s −1 at t 6 d. Despite the lower resolution of our IR data at this time, the IR terminal velocity seems consistent with that in the optical.…”
Section: Expansion Velocitiessupporting
confidence: 58%
See 2 more Smart Citations
“…These were no longer present by day 14.76. In the optical, Skopal et al (2014) found that the Hα line displayed a P Cygni profile, with terminal velocity −1600 km s −1 at t 0.95 d, decreasing to −730 km s −1 at t 6 d. Despite the lower resolution of our IR data at this time, the IR terminal velocity seems consistent with that in the optical.…”
Section: Expansion Velocitiessupporting
confidence: 58%
“…Extensive optical spectroscopy during the early phase was described by Skopal et al (2014). They determined that the effective temperature of the stellar remnant was in the range of 6000-12000 K, and that the stellar remnant was super-Eddington.…”
Section: 3 9 D E L P H I N Imentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the radio and HST images of RS Oph (Hjellming et al 1986;Taylor et al 1989;O'Brien et al 2006;Bode et al 2007;Rupen et al 2008;Sokoloski et al 2008)-the most studied nova blast wave to dateobservations of other novae have shown similar characteristics. Examples include infrared interferometry of V1663 Aql revealing asymmetry (Lane et al 2007), both radio and optical HST observations of light echoes revealing an asymmetric remnant of T Pyx outbursts (Sokoloski et al 2013) together with optical spectroscopy suggesting bipolarity in its 2011 outburst (Shore et al 2013;Tofflemire et al 2013), radio observations of V959 Mon Linford et al 2015) revealing bipolar structure, optical, radio, and X-ray imaging observations of asymmetry in the GK Per nova remnant (Bode et al 2004;Takei et al 2015), and UV spectroscopic and IR interferometric evidence of a bipolar ejection in V339 Del (Schaefer et al 2014;Skopal et al 2014).…”
Section: Collimation and Asymmetrymentioning
confidence: 99%
“…In a recent paper, Skopal et al (2014) have identified a line in the optical spectrum of V339 Del (Nova Del 2013) and other classical novae as the O VI Raman feature at around 6830 Å. Raman scattering is an established radiative process in symbiotic stars. It was first proposed by Nussbaumer et al (1989) to explain the enigmatic 6825, 7083 Å emission line doublet.…”
Section: Introductionmentioning
confidence: 99%